Structural Adjustment Policies in Colombia and Venezuela during the 1980s and 1990s (2020)
This article considers the historical process of admission of stabilization and structural adjustment programs in Colombia and Venezuela in the 80s and early 90s of the twentieth century. This event is considered as the result of a historical process, which acquires particular characteristics in the framework of processes of regulation and capitalist accumulation of these countries in the abovementioned period. It is a descriptive document, based partially on the Treasury Reports of some Colombian Finance ministers and on reports from the Central Bank of Venezuela. The aim is to demonstrate that in the face of the widespread idea of homogenizing the analysis of the application of adjustment programs in the different Latin American countries in this historical period, comparative examination allows highlighting the differences that these processes had in the countries studied. On the other hand, we try to overcome the widespread idea of self-referencing when this type of analysis is done. We conjecture that divergences that characterized these societies and their economies in much of the twentieth century, are deepened by the results of these programs and contribute to explain social, economic and political discrepancies that Colombia and Venezuela show today.